Oxidative metabolism of hexobarbital in human liver: relationship to polymorphic S-mephenytoin 4-hydroxylation - Knodell, R G; Dubey, R K; Wilkinson, G R; Guengerich, F P (The Journal of pharmacology and experimental therapeutics, 1988)
The major route of hexobarbital metabolism in humans involves hydroxylation at the 3'-position followed by oxidation to a 3'-keto metabolite. Studies were performed to characterize the form of cytochrome P-450 responsible for the initial oxidation. In vitro studies indicated that P-450MP purified from human livers, involved in the 4-hydroxylation of S-mephenytoin, efficiently catalyzed the 3'-hydroxylation of hexobarbital; moreover, polyclonal antibodies raised to this enzyme extensively inhibited such activity in human liver microsomes. S-Mephenytoin 4- and hexobarbital 3'-hydroxylase activities in microsomes from different livers were significantly correlated, and both activities were essentially absent in fetal liver preparations. Hexobarbital was also found to inhibit S-mephenytoin 4-hydroxylation and vice versa, with Ki values similar to the Km values for the measured pathways. These data suggested that in vivo metabolism of hexobarbital would be determined by the same genetic factor(s) responsible for polymorphic 4-hydroxylation of S-mephenytoin. This prediction was confirmed by the finding that, after oral administration of a single dose of hexobarbital (300 mg), the 24-hr urinary excretion of 3'-hydroxy- and 3'-ketohexobarbital in a "poor-metabolizer" was only one third of that in a subject of the "extensive-metabolizer" phenotype. Also, the plasma level of metabolites at 6 hr after administration was reduced, and that of unchanged drug was increased in the poor metabolizer. Finally, a markedly enhanced sedative effect was associated with the impaired metabolism. Accordingly, several lines of in vitro evidence indicate that hexobarbital 3'-hydroxylation is catalyzed by P-450MP.